ҚАЗАҚСТАН РЕСПУБЛИКАСЫНДАҒЫ ЖЕРГІЛІКТІ ӨЗІН-ӨЗІ БАСҚАРУ ЖҮЙЕСІ: ҚАЗІРГІ ЖАҒДАЙДАҒЫ ТРАНСФОРМАЦИЯСЫ ЖӘНЕ ДАМУ ПЕРСПЕКТИВАЛАРЫ - R. Yesbergen (Экономика: стратегия и практика, 2019)
The article is devoted to the problem of decentralization of power - the development of the system of local self-government, which is one of the key areas of Kazakhstan’s entry into the top 30 developed countries of the world. Local government is a form of government. This means taking responsibility for local problems and organizing solutions to local problems. The article presents an overview of the foreign experience of the local government system, describes the current situation and identifies its main priorities.The purpose of this article is to determine the directions of development of local government in Kazakhstan on the example of the Aktobe region. When writing the article, methods of analysis and comparison of scientific research were used.The result of the study is the possibility of increasing tax and non-tax revenues in settlements, transferred to the budget of the 4th level in Kazakhstan, for this akims of cities of regional significance and rural districts should have a project mindset.The area of research results is regional, district and rural akimats, offices and departments of economics and budget planning, entrepreneurship and finance.The research results include the development of a democratic society through the development of local self- government according to the Strategy “Kazakhstan-2050”, the successful implementation of the 5-reform “Strong regions and urbanization” of the Medium-term strategic development plan “Strategy-2025”. This contributes to the successful implementation of the national plan. The purpose of this reform is to increase the gross domestic product due to the economic growth of the regions, ensuring the efficient use of available resources.